Doprowadż następujące wyrażenia do prostszej postaci:
a) (x+y)²-(x-y)²+
b) (x+4)²+4(x-1)²=
c) 3(2-y)²+4(y-5)²=
d) 5(3-5a)²-5(3a-7)(3a+7)=
e) (m+1)²+3(m-1)²-5(m+1)(m-1)=
f) (a-1)²-4(a+1)²-6(a+1)(a-1)=
g) -(3+x)²+5(1-x)²-3(1-x)(1+x)=
h) (x-2)(x+2)-(x-3)²+(x+1)²=

2

Odpowiedzi

2009-10-28T17:44:30+01:00
A)x+y*x+y-x-y*x-y
b)x+4*x+4+4*x-1*x-1
c)3*2-y*2-y+4*y-5*y-5
d)5*3-5a*3-5a-5*3a-7*3a+7
e)m+1*m+1+3*m-1*m-1-5*m+1*m-1
f)a-1*a-1-4*a+1*a+1-6*a+1*a-1
g)-3+x*x*3+x+5*1-x*1-x-3*1-x*1+x
h)x-2*x+2-x-3*x-3+x+1*x+1

Nie jestem pewna tej odpowiedzi, ale lepszy rydz niż nic ;)
Najlepsza Odpowiedź!
2009-10-28T19:20:54+01:00
A) X2+2xy+y2-(X2-2xy+ y2 )=x2+2xy+y2-x2+2xy-y2=4xy
b) x2+8x+16+4(x2-x+1)=x2+8x+16+4x2-4x+4=5x2+4x+20
c) 3(4-4y+y2)+4(y2-10y+25)=12-12y+3y2+4y2-40y+100=7y2-52y+112
d) 5(9-30a+25a2)-5(9a2-49)=45-150a+125a2-45a2+245=
80a2-150a+290=8a2-15a+29
e) m2+2m+1+3(m2-2m+1)-5(m2-1)=m2+2m+1+3m2-6m+3-5m2+5=
-m2-4m+9
f) a2-2a+1-4(a2+2a+1)-6(a2-1)=a2-2a+1-4a2-8a-4-6a2+6= -9a2-10a+3
g) -(9+6x+x2)+5(1-2x+x2)-3(1-x2)=-9-6x-x2+5-10x+5x2-3+3x2=
7x2-16x+11
h) (x-2)(x+2)-(x-3)²+(x+1)²= x2-4-(x2-6x+9)+x2+2x+1=
x2-4 -x2+6x-9+x2+2x+1=x2+8x-12